Chemical defense lowers plant competitiveness - Ballhorn, Daniel; Godschalx, Adrienne; Smart, Savannah; Kautz, Stefanie; Schädler, Martin (My University, 2014)
Both plant competition and plant defense affect biodiversity and food web dynamics and are central themes in ecology research. The evolutionary pressures determining plant allocation toward defense or competition are not well understood. According to the growth–differentiation balance hypothesis (GDB), the relative importance of herbivory and competition have led to the evolution of plant allocation patterns, with herbivore pressure leading to increased differentiated tissues (defensive traits), and competition pressure leading to resource investment towards cellular division and elongation (growth-related traits). Here, we tested the GDB hypothesis by assessing the competitive response of lima bean (Phaseolus lunatus) plants with quantitatively different levels of cyanogenesis—a constitutive direct, nitrogen-based defense against herbivores. We used high (HC) and low cyanogenic (LC) genotypes in different competition treatments (intra-genotypic, inter-genotypic, interspecific), and in the presence or absence of insect herbivores (Mexican bean beetle, Epilachna varivestis) to quantify vegetative and generative plant parameters (above and belowground biomass as well as seed production). Highly defended HC-plants had significantly lower aboveground biomass and seed production than LC-plants when grown in the absence of herbivores implying significant intrinsic costs of plant cyanogenesis. However, the reduced performance of HC- compared to LC-plants was mitigated in the presence of herbivores. The two plant genotypes exhibited fundamentally different responses to various stresses (competition, herbivory). Our study supports the GDB hypothesis by demonstrating that competition and herbivory affect different plant genotypes differentially and contributes to understanding the causes of variation in defense within a single plant species.
Keywords: Cyanogenesis; Herbivory; Growth-differentiation balance hypothesis; Lima bean; Tradeoff